Influência do pré-aquecimento na adaptação marginal de dois materiais seladores de fóssulas e fissuras, analisada através de tomografia de coerência ótica - Silva, Célia Alvanir de Aquino (2013)
Among the non-invasive techniques employed in the prevention of caries highlights the sealing pits and fissures which is a conservative maneuver, in order to obliterate them to protect them from attack acid bacteria. Influenced by the studies of pre-heating composite resin, which has experienced great improvement in some of their physical properties, this study aimed to evaluate in vitro the superficial and internal marginal adaptation of different materials and sealants in pre-heating or not. A total of 40 extracted human third molars (n=10) that had their occlusal surfaces prepared to receive sealant. We tested two types of sealing materials: resin sealant (Fluoroshield) and low-viscosity resin (Permaflo), where 50% of previously received heated material and the other half received sealant material at room temperature. All samples were subjected to thermal cycling and pH, simulating a cariogenic oral environment, and later were analyzed appliance OCT (optical coherence tomography). The images obtained alterations were recorded and analyzed statistically. Change was considered as the emergence of bubbles, gaps and cracks in the sealant. Comparisons of the same material, assessing the fact that it is not sealed or preheated material, as well as comparisons between different materials subjected to the same temperature were carried out. The nonparametric Tukey test was used (p < 0,05). The results showed that there was statistically significant difference between both the materials analyzed, as between the situations in which the sealant material was submitted (preheated or not). On the issue of marginal adaptation and internal surface, seen through Optical coherence tomography, may suggest that there is a difference between the use of one type or another of the sealing material analyzed, with superiority attributed to resin Permaflo compared to sealant Fluroshield, telling is the same for the different techniques used